2012
DOI: 10.5754/hge11791
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Stress Responses after Laparoendoscopic Single-Site Hepatectomy: A Perspective Controlled Study

Abstract: LESH is a safe, feasible and minimally invasive approach and has no different impact on stress responses compared to LH. It may be a reasonable alternative to apply in clinical practice by experienced laparoscopic physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…One such study comparing serum levels of tissue injury markers in abdominal and laparoscopic-assisted hysterectomy reported that the laparoscopic group had lower postoperative CRP and CPK values on postoperative days 1 and 2 (21). A more recent study of laparoscopic hepatectomy found that SPLS and MPLS had comparable impacts on the patients' stress responses (22). However, no significant differences in serum marker levels were identified between the SPLS and MPLS groups in the current study.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…One such study comparing serum levels of tissue injury markers in abdominal and laparoscopic-assisted hysterectomy reported that the laparoscopic group had lower postoperative CRP and CPK values on postoperative days 1 and 2 (21). A more recent study of laparoscopic hepatectomy found that SPLS and MPLS had comparable impacts on the patients' stress responses (22). However, no significant differences in serum marker levels were identified between the SPLS and MPLS groups in the current study.…”
Section: Discussioncontrasting
confidence: 70%
“…Several studies are investigating tissue injury following laparoscopic surgery (20)(21)(22). One such study comparing serum levels of tissue injury markers in abdominal and laparoscopic-assisted hysterectomy reported that the laparoscopic group had lower postoperative CRP and CPK values on postoperative days 1 and 2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a non-specific systemic response of the body to various stressful factors such as surgical trauma, general anaesthesia and thermal stimulation [24,25]. Surgery-induced systemic stress response is characterised by endocrine-metabolic changes which are proportional to the severity and duration of postoperative stress response [26].…”
Section: Discussionmentioning
confidence: 99%